Worse prognosis in females with new onset of depression after oral cancer diagnosis: a retrospective case-control study - Hofmann, Elena; Doll, Christian; Rogge, Alize; Preissner, Robert; Heiland, Max; Preissner, Saskia; Koerdt, Steffen (Frontiers in Oncology, 2023)
Background: Sex-related discrepancies in the prognosis of oral cancer patients have not been clarified. This study aimed to assess survival outcomes and potential prognostic factors in female and male patients with oral cancer.A retrospective search of the TriNetX network (TriNetX, Cambridge, Massachusetts, USA) was conducted to identify patients diagnosed with oral cancer (International Classification of Diseases (ICD)-10 codes C02-C06), within the past 20 years from the access date April 21, 2023. Patients were categorized according to sex (female vs. male). Following matching for age and risk factors such as nicotine dependence and alcohol abuse, Kaplan-Meier analysis was performed and risk, odds, and hazard ratios were calculated. Outcome variables were five-year disease-free survival (DFS) and overall survival (OS). Additionally, the female and male patient cohort were compared with regard to the novel diagnosis of depression (depressive episode, major depressive disorder, dysthymic disorder) after the tumor diagnosis.Results: A total of 77,348 patients were assessed. After propensity score matching, 26,578 male and 26,578 female patients were included in each group (mean age 63 years). Disease-free survival (DFS; 71.92% in females vs. 68.29% in males; HR 0.870; p < 0.001) and overall survival (OS; 77.08% in females vs. 71.74% in males; HR 0.793; p < 0.001) were significantly higher in the female cohort. However, in patients diagnosed with depression after the initial cancer diagnosis (n = 4,124), overall survival was worse in female patients compared to male patients (82.48% in females vs. 86.10% in males; HR 1.341; p < 0.001).This retrospective case-control study showed that females with oral cancer had a better DFS and OS than males. However, in females with a newly diagnosed depression after the oral cancer diagnosis, DFS and OS were worse compared to those of male oral cancer patients. Depression may be a relevant prognostic factor that contributes to sex disparities in oral cancer patients.